PENGEMBANGAN APLIKASI E-LEARNING BERBASIS ANDROID UNTUK MENINGKATKAN AKSESIBILITAS PEMBELAJARAN - Nur Aisyah; Cossy Maychandra; Adyanata Lubis; Agung Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Abstract contains a brief description of the research objectives, methods used, instruments, data analysis techniques, and research results. The emphasis of writing abstracts is mainly on research results. Abstracts are written in Indonesian and English. Abstract typing is done single-spaced with margins that are narrower than the right and left margins of the main text. Keywords need to be included to describe the realm of the problem under study and the main terms that underlie the implementation of the research. Key words can be single words or a combination of words. The number of key words 3-5 words. These key words are necessary for computerization. Searching for research titles and abstracts is made easier with these key words.